What does it mean ‘to exist’ in physics? - Heller, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
Physical theories give us the best available information about what there exists. Although physics is not ontology, it can be ontologically interpreted. In the present study, I propose to interpret physical theories à la Quine, i.e. not to speculate about what really exists, but rather to identify what a given physical theory presupposes that exists. I briefly suggest how Quine’s program should by adapted to this goal. To put the idea to the test, I apply it to the famous Hartle–Hawking model of the quantum creation of the universe from nothing, and try to discover what kind of nothingness the model presupposes. I also make some remarks concerning ontological commitments of the method of physics itself.